PENGUATAN KARAKTER SISWA DALAM PEMENUHAN PENDIDIKAN DI ERA DISRUPSI - Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2021)
The world of education in the era of disruption no longer makes teachers and students the only source of knowledge. The era of digitalization will have an impact on students' wrong steps if they are not accompanied by teachers and parents. In the era of disruption, everything can happen very quickly with work leaps that are no longer linear. The purpose of this work is to describe how to position students to build character in entering the era of disruption in absorbing knowledge. The focus of the discussion includes the conditions and tendencies of students in the era of disruption, character education with levels through social networks, learning media for character education in the era of disruption, and synergies in controlling student work patterns. The condition of students in this era of disruption is creative in finding information, as well as the tendency to like news, whether it's true or not, and going viral. Student assistance in the era of disruption is carried out by utilizing social networks. Social networks provide opportunities, space, and movement in facilitating student work on independent and group assignments. The results of the assignment are manifested in the form of reports, presentations, and others as a form of controlled character strengthening development. Character education learning is carried out in a tiered focus so that changes in student behavior will appear in their daily lives. Cooperation in completing tasks is a strength. This situation is able to increase innovation and can synergize. Control of changes in student behavior can be done after carrying out certain tasks / jobs. Thus the form of assistance above is used as an instrument of evaluation and control.